2006
DOI: 10.1007/s00170-005-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational approach to contact fatigue damage initiation analysis of gear teeth flanks

Abstract: The paper describes a general computational model for the simulation of contact fatigue-damage initiation in the contact area of meshing gears. The model considers the continuum mechanics approach, where the use of homogenous and elastic material is assumed. The stress field in the contact area and the relationship between the cyclic contact loading conditions and observed contact points on the tooth flank are simulated with moving Hertzian contact pressure in the framework of the finite element method analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…The full contact width along the face width (Z direction) was 28 mm, the Hertzian contact load width was 2.39 mm and the sample pressure P 0 was 1550 M P a [73,76]. an initial crack.…”
Section: Geometry Of the Gear Tooth And The Load Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…The full contact width along the face width (Z direction) was 28 mm, the Hertzian contact load width was 2.39 mm and the sample pressure P 0 was 1550 M P a [73,76]. an initial crack.…”
Section: Geometry Of the Gear Tooth And The Load Conditionmentioning
confidence: 99%
“…In this case, modeling the occurrence of defects (crack initiation) and the crack propagation are important [76] to accurately predict the service life. Secondly, a defect such as a crack is detected during periodic inspection.…”
Section: Modeling Of Fatigue Crack Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thin hard coatings have positive influences on the fatigue and corrosion fatigue behaviours of the mechanical components, which justifies their uses in some critical systems such as automotive systems [2] and aeronautic systems [3]. Prior to the initiation of the research reported in this paper, it was found that there was a need to develop a more reliable, theoretical and numerical model for the analysis of coating surfaces in the gears, although some effort had been made on the analysis of the fatigue damages of the coated gears [4,5]. To-date, analysis of the coatings in engineering surfaces still largely relies on the uses of empirical formulas or is based on experience.…”
Section: Introductionmentioning
confidence: 99%